BOTULIN THERAPY IN COMPLEX TREATMENT OF CEREBRAL PALSY - Nozila U. Majidova; Kamola A. Kaxarova; Baxtiyorjon Y. Umarov (Central Asian Journal of Medicine, 2024)
Botulinum therapy is one of the important components of the comprehensive treatment of cerebral palsy (cerebral palsy). This study examines the efficacy and safety of botulinum therapy in combination with other rehabilitation methods in children with cerebral palsy. The aim of the study is to evaluate the effectiveness of botulinum therapy in improving motor functions and quality of life in children with cerebral palsy. Materials and methods include an analysis of the results of clinical trials in which children with cerebral palsy underwent botulinum therapy in combination with physiotherapy, speech therapy and other rehabilitation methods. The results of the study provide information on the benefits of botulinum therapy in improving motor skills, reducing muscle spasticity and increasing independence in children with cerebral palsy. In conclusion, the importance of integrating botulinum therapy into the comprehensive treatment of cerebral palsy is emphasized in order to achieve the best results in the rehabilitation of children with this neurological disease. In this article, the authors consider the feasibility of using botulinum therapy in the complex treatment of cerebral palsy.